The impacts of rural digitization on agricultural carbon emission efficiency: evidence from 30 provinces in China over 2011–2022 - Jiang, Weiguo; Chen, Chen (Frontiers in Sustainable Food Systems, 2025)
Under the dual goals of the “dual carbon” and digital rural development strategies, giving full play to the role of rural digitalization to enhance the carbon emission efficiency of agriculture is of great significance to the green and sustainable development of agriculture. Based on the panel data of 30 provinces in China from 2011 to 2022, dynamic spatial Durbin and threshold effect models were used to demonstrate the impact of rural digitalization on agricultural carbon emission efficiency. The results show that: (1) Both of the agricultural carbon emission efficiency and the level of rural digitalization in all provinces in China show a steady upward trend. During the study period, the agricultural carbon emission efficiency in the central region improved the fastest, as well as the rural digitalization level in the western region; (2) Rural digitalization has a significant positive promoting effect on agricultural carbon emission efficiency, and this promoting effect has a spatial spillover effect. Digital development in neighboring rural areas will also improve the carbon efficiency of agriculture in the region. The direct effect is the strongest in the central region, and the spillover effect of the eastern region is the most prominent; (3) The impact of rural digitization on agricultural carbon emissions efficiency has a threshold characteristic. With the improvement of rural digitalization, the promoting effect on agricultural carbon emissions efficiency is more significant. Among the four regions, the threshold value of the rural digital level is the lowest in the eastern region, while in the western region has the highest threshold value. The results of this study provide useful insights for promoting rural digital development, improving agricultural carbon emission efficiency, and promoting agricultural green development.